2020
DOI: 10.3892/etm.2020.9097
|View full text |Cite
|
Sign up to set email alerts
|

Polygonatum sibiricum polysaccharides prevent LPS‑induced acute lung injury by inhibiting inflammation via the TLR4/Myd88/NF‑κB pathway

Abstract: Inflammation plays an important role in cases of acute lung injury (ALI), and the Toll-like receptor 4/nuclear factor-κB (TLR4/NF-κB) pathway, which can be regulated by Polygonatum sibiricum polysaccharides (PSPs), is closely related to the dynamics of lipopolysaccharide (LPS)-induced inflammation. Thus, we sought to evaluate whether or not PSPs prevent LPS-induced ALI by way of inhibiting inflammation via the TLR4/NF-κB pathway in rats. We established an ALI rat model by tracheal instillation of LPS, and by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Furthermore, according to the KEGG database, there are many pathways downstream of CD14/TLR4 receptors ( Fig. 4B ), among which the NF-κB pathway serves a key role in ALI ( 27 , 28 ). Therefore, the mRNA and proteins of the NF-κB pathway were detected using RT-qPCR and WB.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, according to the KEGG database, there are many pathways downstream of CD14/TLR4 receptors ( Fig. 4B ), among which the NF-κB pathway serves a key role in ALI ( 27 , 28 ). Therefore, the mRNA and proteins of the NF-κB pathway were detected using RT-qPCR and WB.…”
Section: Resultsmentioning
confidence: 99%
“…ALI is caused by various direct or indirect factors with the characteristics of diffuse interstitial lung and alveolar edema, about 30% to 50% of the cases are caused by severe infection [ 10 ]. The inflammatory response of lung tissue after ALI can be seen as a series of stress responses of lung tissue to injury, including increased capillary permeability of lung tissue, liquid and plasma protein leakage and a large number of white blood cells migrated to the inflammatory area [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The positive DEX + LPS control group was given dexamethasone 2 mg/kg by intraperitoneal injection 24 h before modeling. In reference to a previous report [ 10 ], for the LPS model group, the positive DEX + LPS control group and the L. casei + LPS experimental group, LPS (2 mg/kg of each mouce, Escherichia coli 055:B5, purchased from Sigma Corporation) was dissolved in 100 μL of normal saline, thereafter injected intraperitoneally to construct ALI model, and the normal group was injected with the same volume (100 μL) of normal saline. After 24 h, mice were euthanized with anhydrous ether, then blood was collected via retro-orbital route and lungs were removed together.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, MYD88 induces the transduction of NF-κB from cytoplasm to nucleus, and initiates gene transcription and protein synthesis of various inflammatory cytokines to regulate the inflammatory responses (Wang et al, 2015). Emerging studies have shown that the TLR4/MYD88/NF-κB signalling pathway is one of the important pathways that regulate inflammatory response, and the activation of this pathway leads to the release of pro-inflammatory factors, including TNF-α, IL-1β, IL-6, IL-10 and IL-12 (Dolinay et al, 2012;Liu, Zhao, et al, 2020;Montravers et al, 1995). Therefore, the downregulation of TLR4/MYD88/NF-κB signal inhibits the inflammatory responses (Liu et al, 2012;Peng et al, 2015;Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%